Melanesian pidgin and second language acquisition - Keesing, Roger M (Lenguas Modernas, 2017)
The development of Melanesian Pidgin English has interesting implications for second language acquisition. First, it has been hypothesized that the development of a pidgin in an interlingual situation parallels the pidgin stage in acquiring a second language. The Pacific case shows the dangers of assuming that superstrate (here, English) is the target language in such situations. Second, the process whereby a developing pidgin is shaped by the grammar of the substrate but lexified mainly from the superstrate is illuminating. Where substrate languages are syntactically similar, grammaticalization can be short-cut: superstrate lexical elements are borrowed to fill substrate grammatical slots. The result of this short-cutting, where new labels are fitted into slots common to substrate languages, is a pidgin highly "effable" (Bickerton) to substrate speakers. Able to calque on their native languages using formulas of morpheme equivalence, they can acquire fluency and gramatical competence extremely easily and quickly.